Basic engineering thermodynamics - Rayner Joel (Longman, 1996)
The book provides a comprehensive introduction to the principles and application of the engineering thermodynamics. It includes systems, the laws of thermodynamics, steam and two-phase systems, gases and single-phase systems, thermodynamic reversibility, entropy. combustion, heat transfer, steam plant, the steam engine, nozzles, steam turbines, air and gas compressors, ideal gas power cycles, internal combustion engines, engine trials, refrigeration and pyschrometry